A Facile Route to the Preparation of Highly Uniform ZnO@TiO2 Core-Shell Nanorod Arrays with Enhanced Photocatalytic Properties. (11th April 2017) - Zhao, Yuanyuan; Tong, Peifei; Ma, Dong; Li, Bing; Liu, Qinzhuang; Chen, San; Zhang, Yongxing
Abstract : Design and synthesis of ZnO@TiO2 core-shell nanorod arrays as promising photocatalysts have been widely reported. However, it remains a challenge to develop a low-temperature, low-cost, and environmentally friendly method to prepare ZnO@TiO2 core-shell nanorod arrays over a large area for future device applications. Here, a facile, green, and efficient route is designed to prepare the ZnO@TiO2 nanorod arrays with a highly uniform core-shell structure over a large area on Zn wafer via a vapor-thermal method at relatively low temperature. The growth mechanism is proposed as a layer-by-layer assembly. The photocatalytic decomposition reaction of methylene blue (MB) reveals that the ZnO@TiO2 core-shell nanorod arrays have excellent photocatalytic activities when compared with the performance of the ZnO nanorod arrays. The improved photocatalytic activity could be attributed to the core-shell structure, which can effectively reduce the recombination rate of electron-hole pairs, significantly increase the optical absorption range, and offer a high density of surface active catalytic sites for the decomposition of organic pollutants. In addition, it is very easy to separate or recover ZnO@TiO2 core-shell nanorod array catalysts when they are used in water purification processes.